(untitled) (Journal of Bangladesh Academy of Sciences, 2012)
Zinc sulphate (ZnSO4.7H2O), an inorganic material has been crystallized by an isothermal evaporation method. ZnSO4.7H2O is highly soluble in water and the solubility is found to be increased almost linearly with the increase of temperature. At room temperature around 34°C, the solubility was found to be 92.41 gm/50 ml. The FT-IR spectroscopy was performed on pure zinc sulphate crystals to identify the presence of functional groups. The grown crystals have been subjected to powder X-ray diffraction to determine the unit cell dimensions and the crystal structure. The lattice parameters are found to be, a = 9.9810 Å, b = 7.2500 Å and c = 24.2800 Å, respectively. The values were in good agreement with those of the reported values. The TGA and DTA study revealed that the grown crystals have good thermal stability. The UV-vis spectrum showed that the material has wide optical transparency in the Ultra-violet region. Key words: Isothermal evaporation; Crystatization; Zinc sulphate; Structural characterization DOI: http://dx.doi.org/10.3329/jbas.v35i2.9426 JBAS 2011; 35(2): 203-210